solution
1) <span>Expand
</span><span>9x−6−12x
2) </span><span>Gather like terms
</span><span>(9x−12x)−6
3) </span> <span>Simplify
</span><span><span>−3x−6</span></span>
Hey!
------------------------------------------------
First Equation:
2x + 3 = -7
2x + 3 - 3 = -7 - 3 (Subtract 7 to both sides)
2x = -10
2x/2 = -10/2 (Divide 2 to both sides)
x = -5
------------------------------------------------
Second Equation:
4.5x - 7 = 20
4.5x + (-7) + 7 = 20 + 7 (Add 7 to both sides)
4.5x = 27
4.5x/4.5 = 27/4.5 (Divide 4.5 to both sides)
x = 6
------------------------------------------------
Third Equation:
-3x + 7 = 28
-3x + 7 - 7 = 28 - 7 (Subtract 7 to both sides)
-3x/-3 = 21/-3 (Divide -3 to both sides)
x = -7
------------------------------------------------
Answers:
2x + 3 = -7 → x = -5
4.5x - 7 = 20 → x = 6
-3x + 7 = 28 → x = -7
------------------------------------------------
Hope This Helped! Good Luck!
Answer:
22.2 ounces
Step-by-step explanation:
18.5 ounces times 1.20
Answer:
<M = 32 and <Y = 103
Step-by-step explanation:
1. Since triangle BCM is congruent to triangle ZYR, we know the corresponding parts of the triangles are congruent. Therefore, <Z = <B = 45. The sum of a triangle’s angles is 180, so <M = 180 - <B - <C = 180 - 45 - 103 = 32
2. This is the exact same diagram, so we can use the information we have collected in #1. Since corresponding parts of congruent triangles are congruent, <Y must be congruent to <C, which equals 103. Therefore, <Y = 103.
I hope this helps! :)